MEDIASI MELALUI ISHLAH SEBAGAI ALTERNATIF PENYELESAIAN PERKARA PERCERAIAN DI PENGADILAN AGAMA (Studi Efektivitas Mediasi di Lombok Timur) - Haeratun '; Seno Wibowo Gumbira (Fakultas Hukum Universitas Sebelas Maret, 2022)
AbstractThe purpose of this scientific writing was to determine and analyze the model of settlement of divorce cases through ishlah in the Religious Courts and to determine the level of success and failure of the settlement of divorce cases through ishlah in the Religious Courts. The research method includes the type of empirical research/socio legal research, while the approach used is a socio legal approach (socio legal approach). The results of this study are that there are several models of settlement of divorce cases through ishlah in the Religious Courts such as; Settlement Mediation, Facilitative Mediation, Evaluative Mediation and Transformative Mediation and also related to the success rate of mediation for divorce cases at the Selong Religious Court and the Taliwang Religious Court is still very low because there are still many mediator judges in the Religious Courts who are not certified so they do not have skills in in seeking peace for the parties, in addition to the inadequate facilities and infrastructure and not having long-distance audiovisual equipment.AbstrakTujuan penulisan ilmiah ini adalah untuk mengetahui dan menganalisis model penyelesaian perkara perceraian melalui ishlah di Pengadilan Agama dan untuk mengetahui tingkat keberhasilan dan kegagalan penyelesaian perkara perceraian melalui ishlah di Pengadilan Agama. Metode penelitian meliputi tipe penelitian empiris/socio legal research,sedangkan pendekatan yang digunakan adalah pendekatan socio legal (socio legal approach). Hasil dari penelitian ini adalah bahwa ada beberapa model penyelesaian perkara perceraian melalui ishlah di Pengadilan Agama seperti; Settlement Mediation, Facilitative Mediation, Evaluative Mediation dan Transformative Mediation dan juga terkait dengan tingkat keberhasilan mediasi perkara perceraian di Pengadilan Agama Selong dan Pengadilan Agama Taliwang masih rendah sekali karena masih banyak hakim mediator yang ada di Pengadilan Agama tersebut yang belum bersertifikat sehingga tidak memiliki skill di dalam mengupayakan perdamaian bagi para pihak, disamping faktor sarana dan prasarananya yang belum memadai serta tidak memiliki audio visual jarak jauh.